Financing nascent industry: Leverage, politics, and performance in Imperial Russia - Amanda Gregg; Steven Nafziger (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper explores the dynamics of corporate finance during the early stages of industrial growth by examining a newly constructed panel database of Imperial Russian industrial corporations' balance sheets. We document large differences in financial strategies and outcomes across industries, over time, over firms' life cycles, and between two Russian corporation types. Russian corporations' profits and dividend payouts followed the Russian business cycle. Russian corporate debt ratios mostly follow mod-ern capital structure theories, but tangible assets were not associated with higher debt levels, suggesting that Russian corporate debt was short-term, that collateral was irrelevant, or that agency problems dom-inated. We also find evidence that investors needed to be compensated for poor protections, since div-idends were valued and widely-held corporations enjoyed greater returns. While the evidence suggests the presence of these and other frictions, our findings are consistent with the Imperial Russian financial system functioning well enough to enable early industrial development.
URN:NBN:fi:bof-202003092012
Keywords: N23; N63; G32; 330; corporate finance; financial history; industrialization; Russia; Russian Empire